The Role of Cannabinoids in Modulating Emotional and Non-Emotional Memory Processes in the Hippocampus - Akirav, Irit (Frontiers in Behavioral Neuroscience, 2011)
Cannabinoid agonists generally have a disruptive effect on memory, learning, and operant behavior that is considered to be hippocampus-dependent. Nevertheless, under certain conditions, cannabinoid receptor activation may facilitate neuronal learning processes. For example, CB1 receptors are essential for the extinction of conditioned fear associations, indicating an important role for this receptor in neuronal emotional learning and memory. This review examines the diverse effects of cannabinoids on hippocampal memory and plasticity. It shows how the effects of cannabinoid receptor activation may vary depending on the route of administration, the nature of the task (aversive or not), and whether it involves emotional memory formation (e.g. conditioned fear and extinction learning) or non-emotional memory formation (e.g. spatial learning). It also examines the memory stage under investigation (acquisition, consolidation, retrieval, extinction), and the brain areas involved. Differences between the effects of exogenous and endogenous agonists are also discussed. The apparently biphasic effects of cannabinoids on anxiety is noted as this implies that the effects of cannabinoid receptor agonists on hippocampal learning and memory may be attributable to a general modulation of anxiety or stress levels and not to memory per se. The review concludes that cannabinoids have diverse effects on hippocampal memory and plasticity that cannot be categorized simply into an impairing or an enhancing effect. A better understanding of the involvement of cannabinoids in memory processes will help determine whether the benefits of the clinical use of cannabinoids outweigh the risks of possible memory impairments.